Prospects of green nanotechnology for efficient management of neurodegenerative diseases - Chaudhary, Vishal (Frontiers in Nanotechnology, 2022)
Current theranostics for neurodegenerative diseases (NDD) management are majorly symptomatic due to a lack of identification of early-stage biomarkers and the inefficiency of drugs to penetrate through the blood-brain barrier. Recently, the Neuro-nanotechnology interface has emerged as a potential strategy for diagnosis, monitoring, and treatment of NDDs owing to smaller particle size, high specific surface area, tunable physicochemical attributes and rich surface functionalities. However, toxicity and biocompatibility are two significant challenges restricting their commercial prospect in NDD management. On the contrary, green nanosystems fabricated using plant extracts, microorganisms, biome-based precursors, repurposed-byproducts, exosomes, and protein-based bio-nanomaterials are economical, eco-friendly, and eco-friendly biocompatible and renewable due to the abundance of biodiversity. This prospect highlight explores the novel and cutting-edge interface of green nanosystems and NDDs for developing diagnostic and implantable devices, targeted drug delivery strategies, surgical prostheses, therapeutics, treatment, nanoscaffolds for neurogeneration, and immunity development. Besides, it discusses the challenges, alternate solutions and advanced prospects of green nanosystems with the integration of modern-age technologies for the development of sustainable green Neuro-nanotechnology for efficient management of NDDs.